Electrospun membrane of bismuth vanadate-polyvinylidene fluoride nanofibers for efficient piezo-photocatalysis applications - Chirag Porwal; Sahil Verma; Manish Kumar; Akshay Gaur; Vishal Singh Chauhan; Rahul Vaish; Imen Kebaili; Imed Boukhris; Hyeong Kwang Benno Park; Yun Hwan Joo; Tae Hyun Sung; Anuruddh Kumar (Scientific Reports, 2023)
Abstract The fabrication of a Poly (vinylidene fluoride) membrane (PVDF) and ceramic-assisted bismuth vanadate-polyvinylidene fluoride (BiVO4-PVDF) composite membrane was achieved through the utilization of the electrospinning technique. The composition and structure of the fabricated membranes were characterized by X-ray powder diffraction, Raman analysis, scanning electron microscopy, Thermo gravimetric analyzer, Fourier transform infrared spectroscopy, and UV–Vis spectroscopy techniques. The prepared polymeric membranes were then utilized for catalytic investigation and to explore, how structure affects catalytic activity using 5 mg/L, 10 mL methylene blue (MB) dye solution. Ultrasonication, visible light irradiation, and the combination were used to study piezocatalysis, photocatalysis, and piezo-photocatalysis, moreover, degradation intermediates were also explored using scavengers. Electrospun BiVO4-PVDF (BV-PVDF) composite has been found to have better piezocatalytic and photocatalytic properties than PVDF. The experimental findings reveal that the composite of BiVO4-PVDF demonstrates the highest efficiency in dye degradation, achieving a maximum degradation rate of 61% within a processing time of 180 min. The rate of degradation was calculated to be 0.0047 min−1, indicating a promising potential for the composite in the field of dye degradation.